Progresso da ferrugem do cafeeiro em clones de Coffea canephora Pierre ex. Froenher - Albane, Rafael Rebelo de Oliveira (2011)
The objective of this study was to do basic studies about epidemiology of coffee rust in clones C. canephora cultivated in field conditions. With specific objectives: 1 - study the temporal progress of rust in different clones of clonal diversity Vitória